Nanostructure-induced colored TiO2 array photoelectrodes with full solar spectrum harvesting. Issue 7 (3rd February 2017) - Liu, Chunlei; Zhou, Wei; Song, Jiakun; Liu, Huijuan; Qu, Jiuhui; Guo, Lin; Song, Guofeng; Huang, Chin-Pao
Abstract : Wedge-shaped colored TiO2 nanoarrays grown on Ti foam have been synthesized with full solar spectrum harvesting. Abstract : Different from regular bandgap narrowing for better sunlight absorption, a series of nanostructure-induced wedge-shaped colored TiO2 array photoelectrodes exhibited full solar spectrum light harvesting and enhanced performances exemplified by photoelectrochemical (PEC) degradation of Ni(ii )–EDTA. Finite element method (FEM) simulation confirmed the influence of the nanostructure towards light absorption in UV, visible, and near-infrared (NIR) regions.